Atividade de micocinas produzidas por Wickerhamomyces anomalus frente às cepas multirresistentes de Acinetobacter baumannii - Junges, Daniele Schaab Boff (2018)
The killer system is the production of substances by yeast killer able to inhibit other microorganisms, this occurs in the natural environment as a way of competition between species by ensuring nutrients. Wickerhamomyces anomalus is a producer of yeast mycocin widely distributed in the environment and resistant to extremes of pH, temperature and osmolarity. Due to these characteristics, this yeast has been used in various industrial processes, especially in the food industry to control contaminants microorganisms. Its action is considered to be minimally toxic to human cells and low potential to induce microorganisms resistance, characteristics that makes the mycocins of W. anomalus an interesting candidate for medical application. Acinetobacter baumannii is a worldwide concern due to its multiresistance, having a high mortality rate and morbidity, especially in hospital environments. This study had as objective to determine the antimicrobial action of mycocins produced by W. anomalus against multiresistant strains of A. baumannii and to evaluate the toxicity of these compounds. The supernatants of WA40, WA45 and WA92 were tested on A. baumannii using the methods of broth microdilution, solid medium test and viability of A. baumannii. To evaluate the toxicity, was made the test of hemolysis and brine shrimp toxicity test. Results evidenced the antimicrobial activity of mycocins of W. anomalus, since even at high dilutions they were able to inhibit A. baumannii. In solid medium, it was possible to observe the formation of zone of inhibition when testing WA40, WA45 and WA92 on A. baumannii, and finally, the viability test showed that in only 3 hours the mycocins of WA45 were able inhibit 100% of the multidrug-resistant cells of A. baumannii followed by 4 h for WA40 and 6 h for WA92. The three supernatants were not cytotoxic when tested on human erythrocytes and Artemia salina. Thus, the micocins of W. anomalus were effective in this study and can be used in the development of new antimicrobial substances.